Suppressing Effect of 2-Nitrobenzaldehyde on Singlet Oxygen Generation, Fatty Acid Photooxidation, and Dye-Sensitizer Degradation - Mahdi Hajimohammadi; Atena Vaziri Sereshk; Clemens Schwarzinger; Günther Knör (MDPI AG, 2018)
2-Nitrobenzaldehyde was found to efficiently block singlet oxygen generation in a series of different test samples upon exposure to UV and visible light under aerobic conditions. The effect of quenching singlet oxygen formation was monitored in the presence of 1, 4-diazabicyclo [2.2.2] octane (DABCO) acting as a well-known singlet oxygen scavenger. A comparison of different nitrobenzaldehyde isomers with other highly effective synthetic antioxidants used in the food industry such as butylated hydroxytoluene (BHT), butylated hydroxyanisole (BHA), tert-butylhydroquinone (TBHQ) revealed that the protection of materials from singlet oxygen decreases in the order of 2-nitrobenzaldehyde > DABCO > TBHQ > 3-nitrobenzaldehyde > BHA > 4-nitrobenzaldehyde > BHT. Upon addition of 2-nitrobenzaldehyde, the oxidation of fatty acids and the degradation of photosensitizers was found to be considerably diminished, which indicates that the presence of 2-nitrobenzaldehyde has a significant protective influence by restricting the singlet oxygen generation and photodegradation of dyes. Moreover, the compound turned out to display its highly suppressing effects on typical singlet oxygen-dependent reactions, such as fatty acid photooxidation and dye photosensitizer degradation, in a rather broad spectral region covering wavelengths from 300 nm (UV-B) to 575 nm (close to the maximum of ambient solar radiation).